2016
DOI: 10.1038/cgt.2016.7
|View full text |Cite
|
Sign up to set email alerts
|

Recipient C6 rs9200 genotype is associated with hepatocellular carcinoma recurrence after orthotopic liver transplantation in a Han Chinese population

Abstract: Hepatocellular carcinoma (HCC) recurrence is one of the leading causes of death after orthotopic liver transplantation (OLT). The sixth complement component (C6) is a late-acting complement protein that participates in the assembly of the membrane attack complex, which has an indispensable role in innate and acquired immune responses, as well as cancer immune surveillance. However, studies assessing the association between C6 and HCC recurrence after OLT are scarce. This study aimed to evaluate the association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…However, as a bridge to the clinic, lots of studies [1619] have shown that implanting human tumor cells orthotopically into the organs of nude mice corresponding to the primary sites in humans results in an increased rate of metastasis in comparison with subcutaneous implantation and orthotopic implantation maybe provide a suitable micro-environment in which ovarian cancer have its intrinsic clinically-relevant properties [16,17,20]. Meanwhile, the orthotopic implantation models have been widely used in several studies on western drugs [21] and traditional Chinese medicines [22–26] as well as bacterial therapies [2730]. In future studies, we will orthotopically implant human ovarian cancer tissues into nude mice and evaluate the function of CFG in these models.…”
Section: Discussionmentioning
confidence: 99%
“…However, as a bridge to the clinic, lots of studies [1619] have shown that implanting human tumor cells orthotopically into the organs of nude mice corresponding to the primary sites in humans results in an increased rate of metastasis in comparison with subcutaneous implantation and orthotopic implantation maybe provide a suitable micro-environment in which ovarian cancer have its intrinsic clinically-relevant properties [16,17,20]. Meanwhile, the orthotopic implantation models have been widely used in several studies on western drugs [21] and traditional Chinese medicines [22–26] as well as bacterial therapies [2730]. In future studies, we will orthotopically implant human ovarian cancer tissues into nude mice and evaluate the function of CFG in these models.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some clinical manifestations and gene mechanisms were shown to be related to post-transplantation prognosis and recurrence. Indeed, tumor size and number, histological grade of differentiation, microvascular and macrovascular invasion, ischemia time, SMO and the C6 genotype are associated with postoperative prognosis and recurrence after OLT ( 2 - 7 , 18 ). However, these factors require invasive or noninvasive assays, which are expensive and/or intolerable.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, orthotopic liver transplantation (OLT) still represents the best tool predicting long-term survival in the treatment of liver malignancy. Clinical prognosis and therapeutic options in HCC after OLT widely depend on both tumor recurrence and hepatic function ( 2 , 3 ). Currently, tumor size, histological grade of differentiation, microvascular and macrovascular invasion, ischemia time, and some related genes are prognostic factors after OLT in patients with HCC ( 4 - 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…[12] Interestingly, we demonstrated that patients with C6 rs9200 GA presented with HCC recurrence following OLT. [13] However, to the best of our knowledge, no research has yet found the association between C6 gene polymorphisms and tacrolimus pharmacokinetics. Therefore, we initially hypothesized that C6 gene polymorphisms might regulate MAC function and mediate tacrolimus metabolism.…”
Section: Introductionmentioning
confidence: 99%